Exploitation of radio direction finder in the design of a UHF transmitter locator system - Jakpar, Muhamad Jamil; Za’bah, Nor Farahidah; Ismail, Ahmad Fadzil; Hasan, Mohammad Kamrul (Indian Society for Education and Environment & Informatics Publishing Limited, 2016)
This paper outlines how the direction finder technology was exploited in the design of a device; capable of locating the where about of a UHF transmitter. The value of amplitude and frequency of the signal were employed in the determination of the signal source direction. The study emphasized on the utilization of low cost components. The assembled prototype offers 22.5° bearing coverage. The determination of the direction was achieved by differentiating the received frequency signal involving multiple antenna arrays. Direction of transmitter was determined by making the receiver antenna arrays emulating condition of motion with the use of antenna switcher. Received signals were converted into tones where larger signal amplitude translates to louder tone. Antenna arrays were arranged in specific manner where the tone volumes were compared and the direction within 360° position was determined. The result suggests that the system can provide the detection coverages up to 22.5 degree which is better than the existing solutions in terms of equipment selection, cost, and coverage.